, “TO BE A JEW” AS A UNIVERSAL SITUATION. VICTOR KLEMPERER’S JEWISH FACULTÉ MAÎTRESSE - Piotrowiak-Junkiert, Kinga (Porównania, 2012)
The philosophical reflection, existing in diary’s of Victor Klemperer, focuses on the issue of Jewish faculté maîtresse. This issue became one of the most important themes of writing in the works of Á. Heller, M. Blanchot, G. Scholem and E. Jabès. These thinkers also considered Shoah and the human spiritual condition in relation to extermination of Jews in time of the Second World War. Imre Kertész makes the ideas of V. Klemperer complete. Kertész formulated a conception of „being a Jew”, which he understand as a universal situation of existence under destructive influence and pressure of the totalitarian dictatorships. Thinking about a „Jewish condition” as a „metaphor of existence” is relevant to various methods of thinking about the self. According to Klemperer and Kertész a Jewish condition means a „negative being” in a superlative degree and also means homeless, writer’s identity and the perception of Scripture as a symbolic, structural system which form all spheres of the writer’s life.